Dental treatment of a patient with Riga- Fede disease. Clinical case report - Munayco Pantoja, Evelyn del Rosario (2018)
Riga-Fede disease is a rare, benign disorder characterized by a reactive ulceration of the oral mucosa, which arises from repetitive traumatic injuries. The constant trauma can cause an ulceration large enough or annoying enough to interfere with proper suction and feeding, which would cause a risk of nutritional deficiencies, dehydration and infections. We have as diagnostic aid, the intraoral radiography, which in infants is taken with the Mannkopf technique. With respect to the treatment of this lesion there is varied information in the literature and it has changed over the years, there are conservative treatments as radicals. We present the clinical case of 7-month-old male infant, who presents with an ulcer on the ventral side of the tongue, with defined edges, approximately 3.5 cm x 2.5 cm in diameter, colored reddish with whitish areas, painful on palpation, with fever and eating problems. He was admitted to the National Institute of Child Health by infectology, where multiple auxiliary examinations were performed, unable to find diagnosis, he was referred to the service of BucoMaxiloFacial Surgery, where his illness was diagnosed and successfully treated.